Extubation of the potentially difficult airway in the intensive care unit. Issue 2 (21st April 2022) - Joffe, Aaron; Barnes, Christopher R.
Abstract : Purpose of review: Extubation in the intensive care unit (ICU) is associated with a failure rate requiring reintubation in 10–20% patients further associated with significant morbidity and mortality. This review serves to highlight recent advancements and guidance on approaching extubation for patients at risk for difficult or failed extubation (DFE). Recent findings: Recent literature including closed claim analysis, meta-analyses, and national society guidelines demonstrate that extubation in the ICU remains an at-risk time for patients. Identifiable strategies aimed at optimizing respiratory mechanics, patient comorbidities, and airway protection, as well as preparing an extubation strategy have been described as potential methods to decrease occurrence of DFE. Summary: Extubation in the ICU remains an elective decision and patients found to be at risk should be further optimized and planning undertaken prior to proceeding. Extubation for the at-risk patient should be operationalized utilizing easily reproducible strategies, with airway experts present to guide decision making and assist in reintubation if needed.